Promoting Philippines as an ESL (English as a Second Language) destination to Koreans - Suplico-Jeong, Luz T. (Animo Repository, 2012)
A survey among 372 South Korean respondents was conducted to determine their assessment of the Philippines as an ESL destination. Four factors were obtained using exploratory factor analysis employing principal factor method. These factors were Course Content, Facilities and Teachers (F1), Philippine Environment (F2), English Advantage (F3), and Cost and Practice Opportunities (F4). Results showed that respondents who have stayed longer in the Philippines with more family members staying with them tend to have higher satisfaction level for F2. Furthermore, female respondents have a significantly higher satisfaction level than male respondents for F3 while no significant differences were observed for F1, F2 and F4.